2014
DOI: 10.3109/09637486.2014.937800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of egg white and its hydrolysate on stearoyl-CoA desaturase index and fat accumulation in rat tissues

Abstract: We investigated the dietary effects of egg white (EW) and its hydrolysate (EWH) on fat metabolism in rats. Wistar rats were divided into casein, EW and EWH dietary groups, and fed their respective diet for 8 weeks. Dietary EW and EWH decreased food intake, body weight gain and fat accumulation in the carcass, liver, muscles and adipose tissues, but muscle weight was increased. In addition, dietary EW and EWH decreased stearoyl-CoA desaturase (SCD) indices and glucose-6-phosphate dehydrogenase activity of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 22 publications
10
29
0
Order By: Relevance
“…EW acted as a pancreas lipase inhibitor and suppressed intestinal TG absorption, resulting in a decrease in liver TG content (26), which was comparable in the present experiment B. Our report previously also showed that the enzymatic activities related to lipogenesis in the liver were suppressed together with lowered liver TG content in rats fed the HFS diet (2). Therefore, EW can be a protein to suppress TG accumulation in the body.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…EW acted as a pancreas lipase inhibitor and suppressed intestinal TG absorption, resulting in a decrease in liver TG content (26), which was comparable in the present experiment B. Our report previously also showed that the enzymatic activities related to lipogenesis in the liver were suppressed together with lowered liver TG content in rats fed the HFS diet (2). Therefore, EW can be a protein to suppress TG accumulation in the body.…”
Section: Resultssupporting
confidence: 73%
“…We have also reported that EWH improves fasting serum glucose and insulin levels in diabetic Goto-Kakizaki (GK) rats (1) and Wistar rats (2). These findings suggest that in addition to improving fat metabolism, EWH can prevent the onset of glucose intolerance and T2DM.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In our previous study, dietary EWH decreased triacylglycerol (TAG) accumulation in muscles and liver in spontaneous diabetic Goto-Kakizaki rats (4). We also showed suppressive effects of EW and EWH on fat accumulation not only in the liver and muscles but also in intra-abdominal adipose tissues and carcasses of normal rats fed a high-fat and high-sucrose diet (HFSD) ad libitum (5). As a potential mechanism, it has been considered that dietary EW and EWH (particularly EW) can suppress food intake, the apparent rate of intestinal fat absorption, and some enzymatic activities in the liver and muscles, which are closely related to fat synthesis.…”
mentioning
confidence: 73%